Transmission of Staphylococcus aureus between health-care workers, the environment, and patients in an intensive care unit: a longitudinal cohort study based on whole-genome sequencing - Price, J; Cole, K; Bexley, A; Kostiou, V; Eyre, D; Golubchik, T; Wilson, DJ; Crook, D; Walker, A; Peto, T; Llewelyn, M; Paul, J (Elsevier, 2016)
Background: Considerable efforts are made to prevent nosocomial transmission of Staphylococcus aureus. Healthcare-workers (HCWs) have been implicated in outbreaks but lack of evidence from non-outbreak situations means that routine HCW screening and S. aureus eradication are controversial. Methods: We performed a prospective observational study to determine how often S. aureus is transmitted from HCWs or the environment to patients on an intensive care/high dependency unit (ICU/HDU) where standard infection control measures were in place. Over fourteen months we systematically sampled HCWs, the environment and patients. Whole-genome sequencing data were used to define subtypes (≤40 single nucleotide variants (SNVs)) and infer recent transmission. Findings: 198 HCWs, 39 environmental locations and 1854 patients were sampled and 1819 isolates sequenced. S. aureus was detected in 29·5-39·7% HCWs at single four-weekly time-points and in 58·1% at least once. Monthly environmental sampling identified S. aureus in 7·7-50·0% of samples. During the study, 605 genetically distinct subtypes were identified (median SNV difference 273 (IQR 162-399)) at a rate of 38 (range 34-42) per month. Only 25 instances of transmission to patients were detected; seven from HCWs, two from the environment, 16 from other patients. Interpretation: In the presence of standard infection control measures HCWs infrequently act as sources of transmission to patients. S. aureus epidemiology in ICU/HDU is characterised by continuous ingress of distinct subtypes rather than transmission of genetically-related strains.